Social impacts of marine protected areas in South Africa on coastal fishing communities. (1st May 2018) - Sowman, Merle; Sunde, Jackie
Abstract: In South Africa, marine protected areas (MPAs) continue to be a favoured tool for biodiversity conservation and fisheries management. Efforts to expand the network of MPAs are contested largely due to historical injustices associated with MPA establishment and the ongoing social impacts linked with their current management and governance. This paper presents findings of recent research on the social dimensions of MPAs in five MPAs in South Africa. Drawing on information gathered from 70 oral histories, over 250 key informant interviews and 28 focus groups, the paper examines key social impacts respondents attribute to MPAs and their establishment and ongoing management. Significant negative impacts reported include the weakening of local governance rights and processes, in particular the lack of effective mechanisms for local community participation in decision-making. The loss of tenure rights and access to resources amongst already marginalised communities has contributed to food insecurity, less exchange of food and less household income. The MPAs investigated have impacted on culture, way of life and sense of place. Yet, despite government commitments to several international policy instruments relevant to MPAs and national laws legislating redress, social issues associated with MPAs have been largely overlooked. Findings from this research demonstrate that the failure to address historical impacts, as well as social hardships and inequities still being experienced, undermine the legitimacy of MPAs and frustrate the achievement of objectives and plans to increase the marine space under protection. Ways of working towards more effective, legitimate and sustainable MPAs in South Africa are suggested. Highlights: Research in five MPAs in South Africa has highlighted a range of social concerns. Loss of tenure rights and restricted access has led to food insecurity, loss of livelihoods and income. Failure to take account of social dimensions including intangible social impacts undermines the legitimacy of MPAs. The success of MPAs in South Africa is influenced by the historical and societal context. Incorporation of social indicators in MPA planning and monitoring is required.